Efforts to Improve Student Learning Outcomes in Fiqh Learning Using LCD Projector Media at MTs Syafi'iyyah Ngaringan - Muhammad Shofi; Nanang Kholidin (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students' learning outcomes in the Fiqh subject with a discussion of the procedures for obligatory prayers in class VII MTs. Syafi'iyyah Ngaringan through the use of LCD projector media. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were students of class VII MTs. Syafi'iyyah Ngaringan. The data for this study were obtained using test and observation techniques. Tests are used to measure student learning outcomes, while observations are used to analyze teacher and student learning activities during the learning process. The data analysis techniques used in this study are quantitative and qualitative descriptive analysis. The results of the study indicate that the use of LCD projector media can improve student learning outcomes, as seen from the significant increase in test scores in each cycle. In addition, the use of this media also has a positive impact on student activity and involvement in the learning process. Thus, the use of LCD projector media can be used as an effective alternative in improving student learning outcomes, especially in Fiqh learning.